MULTIPLE GINGIVAL RECESSION COVERAGE TREATED WITH VISTA TECHNIQUE USING ACELLULAR DERMAL MATRIX (ADM) COMBINED WITH PLATELET RICH FIBRIN (PRF): A CASE REPORT - Rosa Pratiwi; Ernie Maduratna Setiawatie (Odonto : Dental Journal, 2019)
Background: Gingival recession is an exposure of the root surface due to migration of the marginal periodontal tissues apical to the cemento enamel junction. There are so many root coverage procedures, among these techniques, VISTA technique combined with ADM and PRF offers minimally invasive approach.Case Management: A-40-year-old male visited Periodontics Clinic of DentalHospital Airlangga University with the chief complaint of poor aesthetic resulting from exposed root surfaces in upper right front region of the jaw. Root coverage by VISTA technique using ADM combined with PRF was planned to this case.Discussion: The minimal invasive VISTA technique approach, combined with ADMand PRF has a number of advantages for successful treatment of multiple recession defects. VISTA technique was used because it can maintain better blood supply and maintain critical papillary integrity. ADM works like an autogenous graft by providing a bioactive matrix consisting of collagen, elastin, blood vessel channels, and bioactive protein that support natural revascularization, cell repopulation, and tissue remodeling. Growth factors present in PRF plays a crucial role in hard and soft tissue repair.Conclusion: VISTA technique together with ADM and PRF membrane can besuccessfully used as a treatment method for multiple gingival recessions of Miller’s class I defects